Methodological contributions to case study research on management accounting and control - Ferreira, A.; Rodrigues, J. (Tékhne - Review of Applied Management Studies, 2011)
The option for the case study method in management accounting and control research has proved beneficial for the scientific, academic and corporate communities namely by the opportunity to make detailed and close studies of the real corporate world that allow, on one hand, to improve the knowledge of management accounting and control practices and, on the other, to reduce the gap between theory and practice. This article intends to reason on the motives that justify the option for the case study as well as describing the critical issues of this kind of investigation. Notwithstanding the international scientific community acknowledges the contribution of case studies for the management accounting and control area, conclusions indicate that it is necessary to assure that researchers adopt adequate methodological procedures aimed at granting the credibility and quality of the results.